PENGARUH KENAIKAN HARGA BAHAN BAKAR MINYAK TERHADAP KINERJA USAHATANI PADI DI SULAWESI TENGGARA - Syam, Amiruddin (Lampung University)
Rice is an agricultural commodity which has strategic economic value, environmental live, social and political aspect. Several governments makes implication policy on production process for immediately or not especially food crop. The research was done to know the impact of increasing price of fuel on farming system performance in Southeast Sulawesi Province. The data were collected in Konawe and Kolaka as a centre of rice production in Southeast Sulawesi. The result showed that there was in impact on agriculture tools especially tractor rent service, water pump, power thresher and RMU. As the effect on increasing price of fuel, tractor rent price increased to Rp 600.000 (50 %). Operational cost was fully been responsible for farmer, so the profit was be better. The use of water pump is still low. Payment system for service of water pump is sharing holder system, 15 % for pump service and 85 % for farmer. There was no change on sharing composition; the profit obtained by farmer was more increase in relevant with increasing of price of agriculture commodity. The thresher service has change from 6.7 % to 9,1 % and also service of RMU, 1 kg of 11 kg of rice was given to service hulling. Therefore, the effect of increasing fuel was burdened to farmer directly or indirectly, so the farmer position was still lower position.